FAKTOR – FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN PADA PERUSAHAAN SEKTOR AGRICULTURE - NELVIN, NELVIN; WAHYUDI, AGUSTINUS SRI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research aims to determine whether there is an effect of Corporate Tax Rate, Non- debt Tax Shield, Profitability, Firm Size and Asset Tangibility on Leverage in oil, gas and coal companies listed on the Indonesia Stock Exchange for the 2014-2022 period. The research sample consists of 11 companies selected using purposive sampling technique. The research data source comes from the annual financial reports of each company, which are then processed and analyzed using Eviews 10 software. The applied analysis method is panel data regression using a fixed effect model to test hypotheses. The research results show that of the five independent variables studied, there are three variables that have an effect on Leverage, namely Non-debt Tax Shield, Firm Size, and Asset Tangibility. However, the other two variables, Corporate Tax Rate and Profitability, do not have an effect on Leverage.